Selection processes in a citrus hybrid population using RAPD markers - Oliveira, Roberto Pedroso de; Vildoso, Carlos Ivan Aguilar; Machado, Marcos Antônio (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the processes of selection in a citrus hybrid population using segregation analysis of RAPD markers. The segregation of 123 RAPD markers between 'Cravo' mandarin (Citrus reticulata Blanco) and 'Pêra' sweet orange (C. sinensis (L.) Osbeck) was analysed in a F1 progeny of 94 hybrids. Genetic composition, diversity, heterozygosity, differences in chromosomal structure and the presence of deleterious recessive genes are discussed based on the segregation ratios obtained. A high percentage of markers had a skeweness of the 1:1 expected segregation ratio in the F1 population. Many markers showed a 3:1 segregation ratio in both varieties and 1:3 in 'Pêra' sweet orange, probably due to directional selection processes. The distribution analysis of the frequencies of the segregant markers in a hybrid population is a simple method which allows a better understanding of the genetics of citrus group.
Keywords: Citrus reticulata; Citrus sinensis; segregation; genetic markers